Psychometric evaluation of the Dutch language version of the Child and Family Follow-up Survey. (2nd November 2015) - de Kloet, Arend J.; Berger, Monique A. M.; Bedell, Gary M.; Catsman-Berrevoets, Coriene E.; van Markus-Doornbosch, Frederike; Vliet Vlieland, Thea P. M.
Abstract: Aim : The Child and Family Follow-up Survey (CFFS) is developed to monitor long-term outcomes of children and youth with acquired brain injury (ABI). The aim of this study was to translate and adapt it into the Dutch language and to evaluate its reliability and validity. Methods : The CFFS includes the Child and Adolescent Scale of Participation (CASP), the Child and Adolescent Factors Inventory (CAFI) and the Child and Adolescent Scale of Environment (CASE). The CFFS was translated into Dutch following international guidelines and adapted. The internal consistency, validity and test–retest reliability were examined among two groups of patients ( n  = 140 and n  = 27) in the age of 5–22 years with ABI and their parents. Results : The translation and adaptation resulted in the CFFS-DLV, Dutch language version. The CASP-DLV, CAFI-DLV and CASE-DLV had a good internal consistency, with Cronbach's alpha being 0.95, 0.89 and 0.83, respectively. There were statistically significant correlations among the three CFFS subscale scores. These scores were also significantly correlated with the total scores of the Pediatric Quality of Life Inventory (PedsQL, parent) and the Pediatric Stroke Outcome Measure, but not with the domain scores of the Children's Assessment of Participation and Enjoyment (CAPE). The test–retest reliability was good to moderate, with the intra-class correlation coefficients being 0.90 for the CASP-DLV, 0.95 for the CAFI-DLV and 0.81 for the CASE-DLV. Conclusion s: The CFFS-DLV, as translation and adaptation of the CFFS into Dutch, proved to be a promising instrument to measure long-term outcomes of children and youth with ABI. Further research is needed to examine its responsiveness to change and potential in other patient groups.